Parental Care Behavior Of Sumatran Elephants (Elephas maximus sumatranus) During Nocturnal Activities In Gunung Leuser National Park, Tangkahan Resort, Langkat, North Sumatra, Indonesia - Berliani, Kaniwa; C.G Butar butar, Erlin (International Journal of Ecophysiology, 2024)
The Sumatran elephant, active both day and night, is more active two hours before sunset and after dawn. In a matriarchal system, a dominant female leads the herd, with mothers and allomothers (non-nursing females) caring for the calves. This study, conducted at Gunung Leuser National Park, Tangkahan Resort, used CCTV to observe behavior like grooming, feeding, playing, and resting for 12 hours each night. Over 84 hours of observation, 5639 data points were recorded for adults and 5117 for calves, totaling 5040 minutes. Key nighttime activities included grooming (adults: 36.5%, calves: 22.07%), feeding (adults: 33.71%, calves: 24.5%), and playing (calves: 11.8%, adults: 5.24%). The study showed strong mother-calf bonds, with mothers actively protecting and teaching their young. These findings emphasize the mother’s role in the calf's development during nighttime.